Narrativas de pessoas surdas em famílias ouvintes : demandas linguísticas para educação inclusiva - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
Special Education has as its target audience students with disabilities, global disorders and high abilities, among these are students with hearing loss. For deaf students, the teaching of Portuguese is offered in the written modality, as a second language and has the Brazilian Sign Language as the language of instruction. Several discussions are carried out in this sense, mainly focused on the levels of proficiency of deaf students, in relation to the Portuguese language. Thus, the purpose of this research intended to contribute to such discussions in the field of Special Education and aimed to verify whether there are, among deaf students from hearing families, common elements that imply the learning of Portuguese as a second language. The empirical research had its unfolding in the city of Goiânia-GO, with the participation of three students with deafness, who were born in hearing families, and the mothers of these students. Data collection consisted of recording the participants' narratives about their life stories, and the instrument used was the narrative interview, proposed by Clandinin and Conelly (2011). After collection, the data were analyzed using Content Analysis techniques, described by Bardin (1977). Therefore, this is a research with a qualitative approach, which uses the narrative interview as a data collection instrument, which is why it has a certain proximity to phenomenological studies. Because it is a research that considers linguistic, social and pedagogical aspects and therefore drew on studies by Chomsky (1978), Quadros (2011), Cambi (1999), Perlin (2009), Quadros (2006), Skliar (2013), among other authors. Furthermore, the methodological development of the research was based on Petrelli (2004). The research results point out, above all, six common elements among the research participants that may have
Narratives of deaf people in hearing families : linguistic demands for inclusive education
Keywords: Entrevista narrativa; Estudantes surdos; Família ouvinte; Língua portuguesa; Educação especial; Narrative interview; Deaf students; Listener family; Portuguese language; Special education; CIENCIAS HUMANAS::EDUCACAO